Storage Potential and Chemical Composition of Wet Distillers Grains with Solubles (WDGS) Treated with Different Additives - Kavitha, Patakamuri; Ravi, Arunachalam; Rao, Duddu Srinivasa; Reddy, Yeddula Ravindra; Padmaja, Kondeti; Chaitanya, Radha Krishna (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
To study the keeping quality of Wet Distillers Grains with Solubles (WDGS) during 12 days of the storage period, WDGS was treated with  salt, citric acid, lactic acid, propionic acid and sulfuric acid at 1% of DM. No surface spoilage was observed up to 6 days in any of the  treatments and up to 12 days in propionic and sulfuric acid treated WDGS. Mean pH was significantly lower (p
Keywords: Additives; Chemical composition; Keeping quality; WDGS